2008
DOI: 10.1063/1.3021081
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pulse thermal damage thresholds of materials for x-ray free electron laser optics investigated with an ultraviolet laser

Abstract: Optical elements to be used for x-ray free electron lasers (XFELs) must withstand multiple high-fluence pulses. We have used an ultraviolet laser to study the damage of two candidate materials, crystalline Si and B4C-coated Si, emulating the temperature profile expected to occur in optics exposed to XFEL pulses. We found that the damage threshold for 105 pulses is ∼20% to 70% lower than the melting threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…The spot is not visible in AFM, indicating that the surface change associated with the damage site is either very gradual toward the edge or the edge height is less than 0.1 nm. In the UV experiments on B 4 C films, a gradual decrease of the damage threshold with increasing number of pulses was found [13], whereas in the x-ray experiments the transition occurred more abruptly between 10 3 and 10 4 pulses. Figure 4 shows SEM pictures of a 1 μm SiC film after exposure to the XFEL beam.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The spot is not visible in AFM, indicating that the surface change associated with the damage site is either very gradual toward the edge or the edge height is less than 0.1 nm. In the UV experiments on B 4 C films, a gradual decrease of the damage threshold with increasing number of pulses was found [13], whereas in the x-ray experiments the transition occurred more abruptly between 10 3 and 10 4 pulses. Figure 4 shows SEM pictures of a 1 μm SiC film after exposure to the XFEL beam.…”
Section: Resultsmentioning
confidence: 97%
“…This is close to the melt threshold of 2.2 to 2.6 J/cm 2 , calculated from the x-ray absorption cross section [11] and the thermodynamic properties of B 4 C [12]. In previous experiments using a UV laser, it was found that the multiple-pulse damage threshold for B 4 C lies below the single-pulse damage threshold [13]. We performed similar experiments on bulk B 4 C at 0.83 keV, exposing the same spot up to 10 4 times.…”
Section: Resultsmentioning
confidence: 99%
“…A definitive experimental verification of these models has not been performed since appropriate light sources are not yet available. Instead, existing light sources have been used to test the models by emulating the effect of x-ray FEL radiation, 11,12 but they are operated typically at wavelengths longer than 32 nm, making extrapolation to x-ray FEL conditions questionable. In this paper we determine the robustness of optical materials that will be used at LCLS, at wavelengths as short as 13.5 nm at FLASH.…”
Section: Wavelength Dependence Of the Damage Threshold Of Inorganic Mmentioning
confidence: 99%
“…Recently, several damage studies at the grazing incidence condition in the hard X-ray regime were reported for single shots (Aquila et al, 2015;Koyama et al, 2013a). There have been some multi-shot studies in the ultraviolet (Hau-Riege et al, 2008) and extremeultraviolet or soft X-ray regimes (Juha et al, 2009;Sobierajski et al, 2016), which were carried out for normal incidence conditions and for non-metallic materials. However, investigations of damage due to multi-shot exposure of ultra-short intense X-ray pulses and at grazing incidence conditions have not been reported yet in the literature, except of our recent studies on platinum coating at 900 eV photon energy (Krzywinski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%